Challenges in teaching Arabic at the elementary level: A case study of Madrasah Ibtidaiyah Tarbiyatul Huda Malang - Taufiqurrochman, R.; Nabia, Alva Solla; Camelia, Navila; Khodijah, Siti (Abjadia : International Journal of Education, 2025)
The teaching of Arabic at the elementary level, particularly in Madrasah Ibtidaiyah (MI), faces various challenges that affect its effectiveness. This study aims to identify the main challenges in teaching Arabic at MI Tarbiyatul Huda Mergosono Malang as a representation of schools with limited resources. A descriptive qualitative approach with a case study design was used to collect data through interviews, observations, and documentation. The findings reveal that the primary challenges include low teacher competency, lack of student motivation, limited learning facilities, suboptimal curriculum implementation, and minimal external support from parents and the government. These factors are interconnected, creating a vicious cycle that is difficult to break without strategic intervention. Based on these findings, several recommendations are proposed, such as intensive teacher training, the provision of relevant learning media, and collaborative programs involving schools, parents, and the government. This research provides practical insights for improving the quality of Arabic language teaching in MIs with similar conditions, thereby fostering a generation that not only understands Arabic as a means of worship but also as a tool for global communication.